A three-dimensional LiVPO4F@C/MWCNTs/rGO composite with enhanced performance for high rate Li-ion batteries. (1st December 2018) - Hu, Guorong; Gan, Zhanggen; Cao, Yanbing; Du, Ke; Du, Yao; Peng, Zhongdong
Abstract: Lithium vanadium fluorophosphate (LiVPO4 F) composite with three-dimensional conductive networks architecture is synthesized with synergistic modification of pyrolytic carbon (C), multi-walled carbon nanotubes (MWCNTs) and graphene sheets (rGO). The differences between LiVPO4 F@C, LiVPO4 F@C/MWCNTs, LiVPO4 F@C/rGO and LiVPO4 F@C/MWCNTs/rGO composites are compared through a variety of characterization means. By means of SEM and TEM analysis, it can be seen that pyrolyzed C, MWCNTs and rGO are interwoven, which forms a three-dimensional conductive network structure wrapping the LiVPO4 F particles. The difference of discharge specific capacity between LiVPO4 F@C and LiVPO4 F@C/MWCNTs/rGO composites is becoming larger and larger with the increase of charge-discharge rate. Additionally, CV and EIS results indicate that the LiVPO4 F@C/MWCNTs/rGO has the smallest polarization value and charge transfer impedance (Rct ) as well as the highest diffusion coefficient of lithium ion (DLi+ ) in all samples. Consequently, LiVPO4 F@C/MWCNTs/rGO composite exhibits a high rate capability (97.9 mAh/g cycles at 10 C) and cycling stability (93.74% capacity retention over 800 cycles at 10 C)，showing potential application for high power LIB with high voltage. Highlights: A three-dimensional conductive network of LiVPO4 F@C/MWCNTs/rGO composite is synthesized by a modified solid state method. An ideal architecture hybrid cathode material with 3D ion/electron diffusion channels is constructed. LiVPO4 F@C/MWCNTs/rGO composite exhibits a high rate capability and cycling stability.